Penerapan Algoritma Decision Tree dalam Klasifikasi Data “Framingham” Untuk Menunjukkan Risiko Seseorang Terkena Penyakit Jantung dalam 10 Tahun Mendatang - Raharja, Agung Rachmat; Jayadi; Pramudianto, Angga; Muchsam, Yoki (Pt. Anagata Sembagi Education, 2024)
Heart disease is one of the deadliest diseases in Indonesia and in the world, many of the sufferers do not know the risk of heart disease. This research will analyze and identify factors that will affect the risk of heart disease. With the decision tree algorithm approach which is one of the methods of machine learning that can produce predictive models based on a series of logical decisions. The application is done by classifying framingham data to assess the risk of heart disease in the next 10 years. The result is a Decision Tree model used to predict the risk of heart disease based on the Framingham dataset. The model achieved 74% accuracy on the test data